University Students' Perception of Indonesian Language Learning Innovation-Based Podcast - Hidayati Azkiya; Ilya Husna; Ade Sri Madona; Risa Yulisna; Dian Shaumia; Dina Fitria Handayani (AL-ISHLAH: Jurnal Pendidikan, 2024)
In the evolving landscape of digital education, integrating innovative tools into language learning is crucial for enhancing student engagement and accessibility. This study examines the incorporation of podcasts, defined as episodic digital audio content accessible via the internet, in Indonesian language learning at the university level. Utilizing a descriptive qualitative methodology, the research focuses on 32 students from the Indonesian Language Education program at Bung Hatta University. Despite general familiarity among students with podcasts, their application as an educational tool for Indonesian language instruction is infrequent within this program. Data were collected through surveys comprising multiple-choice and essay questions, administered through Google Forms. Findings suggest a need for Indonesian language educators to more actively integrate podcasts into their teaching strategies, leveraging this medium's potential to enhance accessibility and engagement in language learning. The implications of this research highlight the importance of adopting digital audio content as a complementary tool in language education, encouraging educators to explore innovative methods to enrich the learning experience and improve student outcomes.